2022
DOI: 10.1186/s13643-022-01963-y
|View full text |Cite
|
Sign up to set email alerts
|

The effect of lead exposure on IQ test scores in children under 12 years: a systematic review and meta-analysis of case-control studies

Abstract: An inevitable exposure to the toxic heavy metal such as lead in our environmental can have irreversible effects on children’s mental performance.In this study, 3316 children in 8 case-control studies were selected for review. The case group was exposed to a concentration of lead above 10 μg/dL, and the control group was exposed to a concentration of less than 10 μg/dL, but the duration of exposure was different among studies, and the subgroup analysis was performed based on this variable.In the subgroup with d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 27 publications
(23 reference statements)
0
2
0
Order By: Relevance
“…Including the systematic review and meta-analysis of case-control studies were provided by investigations from different countries over the world. This study also demonstrated that the concentration of lead exposure had a large effect on mental function in children under 12 years [3].…”
Section: Blood Lead Level and Cognitive Performance In Ukrainian Scho...supporting
confidence: 62%
See 1 more Smart Citation
“…Including the systematic review and meta-analysis of case-control studies were provided by investigations from different countries over the world. This study also demonstrated that the concentration of lead exposure had a large effect on mental function in children under 12 years [3].…”
Section: Blood Lead Level and Cognitive Performance In Ukrainian Scho...supporting
confidence: 62%
“…Especially adverse effects of lead on the mental function. The new systematic review and meta-analysis of casecontrol studies demonstrate the large effect of lead exposure on IQ test scores in children under 12 years [3]. The World Health Organization estimate that lead exposure causes 30% of the global burden of idiopathic intellectual disability [4].…”
Section: Blood Lead Level and Cognitive Performance In Ukrainian Scho...mentioning
confidence: 99%
“…Lead phosphate is absorbed by the brain, liver, spleen, kidneys, and spinal cord and then redistributed to other body parts sensitive to its effects (Balali-Mood et al, 2021). The body's lead contamination can damage IQ (Heidari et al, 2022;Hou et al, 2013;Levinschwartz et al, 2020;Schwartz, 1994). Children infected with up to 10 micrograms of Pb can become idiots.…”
Section: Introductionmentioning
confidence: 99%
“…Some elements are toxic at very low concentrations, e.g., Pb, Cd, Hg, As, Mo, Be, Ga, Sb, radon (Rn), Bi, and polonium (Po). It has been documented that an increase in environmental Pb is directly proportional to a decrease in IQ in children [ 18 ]. The adverse effects of overexposure to metals and metalloids such as Al, Sb, As, Ba, Be, Bi, B, Cd, Cr, Co, Cu, Ga, indium (In), Ge, gold (Au), Fe, Pb, Li, Mn, Hg, Mo, Ni, niobium (Nb), tantalum (Ta), platinum (Pt), palladium (Pd), iridium (Ir), Rh, osmium (Os), ruthenium (Ru), yttrium (Y), lanthanum (La), Se, Ag, tellurium (Te), thallium (Tl), Sn, Ti, tungsten (W), V, Zn, Zr and hafnium (Hf) are well known in occupational medicine.…”
Section: Introductionmentioning
confidence: 99%